STUDI KASUS PADA IBU HAMIL TRIMESTER III DENGAN KEHAMILAN POSTDATE DI PMB “S” JETIS PONOROGO - Indah Dian Nirwana; Hayun Manudyaning Susilo; Ririn Ratnasari (Health Sciences Journal, 2022)
pPostdate pregnancy is one of the great danger pregnancies, this can cause more serious risk and confusions for both the mother and the embryo during pregnancy, labor or post pregnancy. Postdate pregnancy is a pregnancy that surpasses the assessed day of birth (HPL) with a gestational time of 40-42 weeks. The motivation behind this investigation was to give coherence of care to Mrs. W G2P10001 in PMB "S" Jetis Ponorogo. The strategy utilized in this exploration is expressive subjective with contextual analyses and the plan utilized is field perception by gathering information utilizing different strategies by talking, noticing and reporting maternity care and portraying the consequences of contextual investigations. In view of the consequences of the contextual investigations, information acquired that the effect on the mother will frequently be experienced like delayed work, removal, uterine idleness, shoulder dystocia, broad tearing of the birth waterway, placental inadequacy and post pregnancy drain. In this manner, midwifery are relied upon to give IEC to pregnant ladies about HPHT, factors that cause post-date pregnancy and dangers during conveyance with post-date pregnancy, in order to limit the impact of dangers and complexities during conveyance and backing the wellbeing of pregnant ladies with post-date by advancing the execution of care. obstetrics in postdate pregnancy with SOAP obstetric administration. Keywords: pregnant ladies, postdate